A arbitragem nos conflitos envolvendo a administração pública: uma proposta de regulamentação - Schmidt, Gustavo da Rocha (2016)
On May 26, 2015, the Brazilian legislature enacted Law n. 13.129/2015, modifying the Brazilian Arbitration Law (Law n. 9.307/1996), allowing public entities, under § 1st of article 1 of the Brazilian Arbitration Act, not only to settle disputes concerning property rights by arbitration, but also to insert the corresponding arbitration clause in public contracts in general. One of my goals, in this paper, it to provide a better understanding of the scope of the rule laid down in article 1st, § 1, of Law n. 9.307/96, offering a deep explanation of the regulatory framework regarding the arbitration act and its applications to the Brazilian public sector. At the end, I intend to indicate a course of action aimed at promoting the use of arbitration in disputes involving Brazilian administrative agencies. Moreover, I intend to present a draft of an executive decree, directed to regulate arbitration within the state bureaucracy.